Partial characterization of a malonyl-CoA-sensitive carnitine O-palmitoyltransferase I from Macrobrachium borellii (Crustacea: Palaemonidae) - Lavarias, Sabrina Maria Luisa (2009)
The shuttle system that mediates the transport of fatty acids across the mitochondrial membrane in invertebrates has received little attention. Carnitine O-palmitoyltransferase I (EC 2.3.1.21; CPT I) is a key component of this system that in vertebrates controls long-chain fatty acid β-oxidation. To gain knowledge on the acyltransferases in aquatic arthropods, physical, kinetic, regulatory and immunological properties of CPT of the midgut gland mitochondria of Macrobrachium borellii were assayed. CPT I optimum conditions were 34 °C and pH = 8.0. Kinetic analysis revealed a Km for carnitine of 2180 ± 281 μM and a Km for palmitoyl-CoA of 98.9 ± 8.9 μM, while Vmax were 56.5 ± 6.6 and 36.7 ± 4.8 nmol min− 1 mg protein− 1, respectively. A Hill coefficient, n ~ 1, indicate a Michaelis–Menten behavior. The CPT I activity was sensitive to regulation by malonyl-CoA, with an IC50 of 25.2 μM. Electrophoretic and immunological analyses showed that a 66 kDa protein with an isoelectric point of 5.1 cross-reacted with both rat liver and muscle-liver anti CPT I polyclonal antibodies, suggesting antigenic similarity with the rat enzymes. Although CPT I displayed kinetic differences with insect and vertebrates, prawn showed a high capacity for energy generation through β-oxidation of long-chain fatty acids.